2002
DOI: 10.1016/s0272-6963(02)00024-4
|View full text |Cite
|
Sign up to set email alerts
|

Toward a theory of project interdependencies in high tech R&D environments

Abstract: In today’s intensely competitive market place, high technology firms are challenged with the task of managing multiple‐concurrent research and development (R&D) projects with constrained resources. As success in the business world depends on the ability to do more with less, it is important for these high technology firms to understand why certain projects consume less monetary resources but still achieve superior product development outcomes. To address this question, we develop a theoretical framework for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 27 publications
0
100
0
4
Order By: Relevance
“…However, projects are often interdependent, and the literature highlights a range of types of interdependencies, such as resource and technical dependencies, and dependencies based on learning and organizational structures (Jerbrant, 2013, Parker et al, 2015, Verma and Sinha, 2002, Eilat et al, 2006, Blau et al, 2004, Killen and Kjaer, 2012, Bathallath et al, 2016. Understanding these interdependencies is important because they can result in flow-on effects throughout the portfolio, stemming from decisions or problems related to individual projects (Aritua et al, 2009, Collyer andWarren, 2009).…”
Section: Literature Review Ppm Decision Making and Project Interdepenmentioning
confidence: 99%
“…However, projects are often interdependent, and the literature highlights a range of types of interdependencies, such as resource and technical dependencies, and dependencies based on learning and organizational structures (Jerbrant, 2013, Parker et al, 2015, Verma and Sinha, 2002, Eilat et al, 2006, Blau et al, 2004, Killen and Kjaer, 2012, Bathallath et al, 2016. Understanding these interdependencies is important because they can result in flow-on effects throughout the portfolio, stemming from decisions or problems related to individual projects (Aritua et al, 2009, Collyer andWarren, 2009).…”
Section: Literature Review Ppm Decision Making and Project Interdepenmentioning
confidence: 99%
“…Interdependencies may be classified in different ways. For instance, [53] mentioned three origins of interdependencies including: resources shared by different Projects, a single technology developed by different Projects and market conditions having an effect on objectives and specifications of different Projects.…”
Section: Portfolio Riskmentioning
confidence: 99%
“…They found that there is a technology push factor related to the development of biotechnology and, the demand pull related to the growing R&D performance required by the market. Verma and Sinha (2002) developed a theoretical framework for understanding the interdependencies between project and their relationship to project performance, based on the Fortune 500 high-tech manufacturing firm, in a multiple-concurrent R&D environment. Niosi and Banik (2005) work was based on 90 Canadian-based publicly quoted biotechnology companies.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…The price of assets is a proxy and is obtained by the interest level. Dividing the sum of R&D expenses into net business revenues derives the price of R&D expenses Verma and Sinha (2002). Literature affirms the assumption that most firms operate with variable returns to scale rather than constant returns to scale, hence it is considered practical to present CRS as well as VRS results to add richness of the analysis.…”
Section: Data Employed and Its Characteristicsmentioning
confidence: 99%